2001
DOI: 10.5694/j.1326-5377.2001.tb143704.x
|View full text |Cite
|
Sign up to set email alerts
|

The intention to hasten death: a survey of attitudes and practices of surgeons in Australia

Abstract: Objective To determine attitudes among surgeons in Australia to assisted death, and the proportion of surgeons who have intentionally hastened death with or without an explicit request. Design Anonymous, cross‐sectional, mail‐out survey between August and November 1999 Participants 683 out of 992 eligible general surgeons (68.9% response rate). Main outcome measures Proportion of respondents answering affirmatively to questions about administering excessive doses of medication with an intention to hasten death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 15 publications
2
35
0
1
Order By: Relevance
“…At the same time, there had been a slight increase in the proportion of doctors who report having administered drugs with the intention of hastening death. On this issue, we also note a point of agreement between our findings and the results obtained by Douglas et al 7 in a study to “determine attitudes among surgeons in Australia to assisted death, and the proportion of surgeons who have intentionally hastened death”. Those authors reported that 36% of surgeons surveyed responded affirmatively to the following question:…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, there had been a slight increase in the proportion of doctors who report having administered drugs with the intention of hastening death. On this issue, we also note a point of agreement between our findings and the results obtained by Douglas et al 7 in a study to “determine attitudes among surgeons in Australia to assisted death, and the proportion of surgeons who have intentionally hastened death”. Those authors reported that 36% of surgeons surveyed responded affirmatively to the following question:…”
Section: Discussionsupporting
confidence: 91%
“…21 It is noteworthy that a more recent survey of surgeons by Douglas et al revealed even higher levels of voluntary and nonvoluntary euthanasia. 22 For the purposes of the discussion at hand, the results of this survey are less significant than the findings of the Kuhse-Singer survey. The respondents to the Kuhse-Singer survey came from 27 different medical disciplines.…”
Section: The Findings Of the Survey -High Rate Of Non-voluntary Euthamentioning
confidence: 69%
“…Some empirical research on this issue has seemed to support this suspicion. For example, a recent study by Douglas et al 6 found that physicians in Australia had difficulty deciding whether a consequence of their interventions (the death of their patient) was an intended or unintended event 11. To our knowledge, no empirical work has been done on the possible causes of the alleged uncertainty of these intention–ascriptions.…”
Section: Introductionmentioning
confidence: 99%
“…They have claimed that clinical intentions are frequently “ambiguous” and multiple 4 5 6. They have also suggested that clinicians frequently have difficulty identifying what their intentions are in a given case.…”
mentioning
confidence: 99%